Effect of cognitive bias modification training on body image dissatisfaction in adolescents with anorexia nervosa or depression—a pilot feasibility randomized controlled crossover study - Glombitza, Eva; Cornelissen, Piers L.; Tovée, Martin J.; Legenbauer, Tanja (Frontiers in Psychology, 2025)
IntroductionBody image disturbance presents transdiagnostically with an impact on the development and maintenance of psychiatric disorders. Addressing body image disturbance, a cognitive bias modification training (CBM) was developed using a two-alternative forced choice task (2-AFC) to alter patients’ individual perceptual boundary between what they classify as a fat versus a thin body. This pilot study aimed to evaluate, for the first time, the paradigm’s feasibility and efficacy in adolescents in a clinical context.MethodsThis pilot study included adolescent inpatients aged 13–17 years diagnosed with (atypical) anorexia nervosa (n = 12) or depression (n = 17), representing two prevalent disorders in adolescence. The 2-AFC task was tested in this population for the first time. Designed as a randomized crossover trial, patients underwent a 4-day intervention with corrective feedback and a 4-day control with confirmatory feedback. Psychometric measures assessing body image disturbance, depressive symptoms, and general psychopathology were collected at the beginning of the training and 10 days afterward (day 1, 15, 29).ResultsMixed ANOVAs showed that the 2-AFC CBM paradigm significantly shifted the categorical boundary over 10 days, altering patients’ individual perceptual boundary but did not improve the body image specific psychometric measures. Linear regression indicated training effects on diagnosis-specific characteristics, and t-test comparisons revealed improved depression-specific symptoms for the depression group. The control condition had a non-neutral effect and shifted the individual boundary to a lower body mass index (BMI), particularly in patients with anorexia.DiscussionThese findings confirm the feasibility and effectiveness of the 2-AFC CBM paradigm in adolescent inpatients transdiagnostically with further larger randomized controlled effectiveness trials required. The study suggests including normal-weight patients with anorexia nervosa only and not using confirmatory feedback as a control condition, but as an orientation and confirmation of a healthy weight limit.